Synthesis Of Crosslinked Polyvinyl Alcohol Ultrafiltration Membrane For Treatment Of Latex Wastewater - Yusuf, Nuruzaikha Muhammad (2013)
Membrane separation technologies particularly in the ultrafiltration, nanofiltration and reverse osmosis are progressively more focused on finding the suitable solutions for lessening and mitigating the irreversible membrane fouling. Fouling is a serious hindrance to the development and application of the membrane science and technology. Essential research is also being done on the surface modification based on the hydrophilicity principle. By increasing the membrane surface hydrophilicity, this will generally improve the membrane resistance to fouling. This thesis focuses on the preparation, characterization and the performance evaluation of crosslinked Polyvinyl Alcohol (PVA) membrane towards ultrafiltration process. Formation of the flat sheet membrane had been produced by modifying polymer concentration, crosslinking temperature and crosslinking duration. PVA is highly hydrophilic and has excellent film-forming and chemical resistance properties. Chemical crosslinking is the most common approach for stabilizing PVA membranes, which makes it less swollen in the water. Asymmetric PVA membranes were prepared by the immersion-precipitation technique and were further crosslinked with glutaraldehyde (GA). Detailed studies on membrane formulation (polymer concentration) and crosslinking condition (duration and temperature) had been carried out.